Fatores determinantes das diversidades beta taxonômica e funcional do zooplâncton em planícies de inundação neotropicais. - Amaral, Diogo Castanho (2020)
Abstract: Freshwater ecosystems are changing their natural conditions, influenced and accelerated by human activities. These processes are capable of changing the hydrological regime and the composition of the communities, letting the future of aquatic biodiversity unknown. The construction of dams has been one of the main factors responsible for environmental changes, such as nutrients depletion, increased water transparency and loss of biodiversity in freshwater ecosystems. The aim of our study was to analyze the functional and taxonomic dissimilarity of the zooplankton community and its drivers in response to the effect of the hydrological cycle (drought and rainy), in two highly distinct floodplains, the Upper Paraná River (river with a cascade of dams) and the Amazon. A total of 72 samples were collected (16 AMA dry and 16 on rainy and 20 PAR dry and 20 on rainy) from zooplankton communities as the response variable, phytoplankton as a predictor of food, fish as a predictor of potential predators and limnological variables. Were calculated ?-Total diversity and partitioned in the components ?-Repl and ?-Rich (taxonomic and functional approach). We expect that environmental heterogeneity is going to drive higher values of beta diversity. In sequence, distance-based redundancy analysis (db-RDA) was calculated using the distance matrices generated in the functional and taxonomic beta to assess which are the determinants of zooplankton beta diversity. Thus, we hypothesized that biotic interactions will have stronger relationships with zooplankton dissimilarity during the drought and, limnological variables and spatial component will be more important during rainy season. Greater environmental heterogeneity was found in the Amazon floodplain and also in the dry season. The beta functional and taxonomic diversity of zooplankton showed a similar relationship between the floodplains and between the hydrological periods, represented by the ?-Repl component, except for the drought season in the Upper Paraná River, where the functional diversity showed the lowest values, undetected by the taxonomic approach. The factors that influenced the zooplankton beta functional and taxonomic diversity in the two floodplains were different depending on the hydrological period, reflecting once again the difference in environmental heterogeneity and the strength of hydrodynamics within each plain. The analysis of the species and functional traits distribution and, which are the variables structuring this distribution is extremely important to analyze ecosystem processes and services, especially in impacted environments such as the Upper Paraná River floodplain, and a floodplain so biodiverse as the Amazon, and even so, with the prediction of the construction of numerous dams in its hydrographic basin. We reinforce the importance of periodic flooding in these floodplains, for the maintenance of biodiversity and ecosystem services over time, and in this way, prevent biotic homogenization, and consequently, conserve these aquatic ecosystems.